The Role of the Human Development Index in Moderating the Effect of Household Consumption Expenditure, Government, and General Population Consumption Expenditure on Economic Growth (Universitas Negeri Semarang, 2022)
Economic growth is used to assess economic performance, especially to analyze the results of economic development efforts undertaken by districts/cities of Central Java Province. This research examined the role of the human development index in moderating household consumption expenditure, government expenditure, and population on economic growth from the perspective of economic growth theory. This research design used a quantitative approach with panel data. The number of observations used in this study was 175 analysis units, consisting of time series data from 2017 to 2021 and cross-data from 35 districts/cities in Central Java Province. Data had obtained from the Central Bureau of Statistics and the Regional Finance and Asset Management Department. Data analysis used descriptive and inferential analysis with Moderate Regression Analysis (MRA) absolute differences test. The results showed that household consumption expenditure and government expenditure had a positive and significant effect, while the population did not affect economic growth. In addition, the human development index variables had used to moderate household consumption expenditure's impact on economic growth. However, the human development index has not been able to moderate the effect of government expenditure and the population on economic growth. This research had expected to enrich the treasury of science and the theory of classical economic growth on economic growth and as a basis for policy in the government world. In particular, the economic development of Central Java became a guide in increasing economic growth.